ECONOMIC ANALYSIS OF PRODUCTION OF HARAD (TERMINALIA CHEBULA) AND CONSTRAINTS FACED IN JAMMU - Choudhary, Dr Punit (Indian Forester, 2022)
The present study analysed cost and returns of Harad and is conducted during the year 2019-20 in the different blocks of Jammu district. The blocks selected are the major Harad producing areas of Jammu district and produce from these blocks are transported to Amritsar Mandi for further export to Arab countries. A sample of 60 farmers from four blocks Mathwar, Rabta, Bhalwal and Ranjan were selected randomly. Average total variable and fixed cost per year was `74570.58 per 100 plants. The cost of cultivation increases due to higher cost incurred on human labour. Net returns varied from Overall net returns for 100 trees varied from over cost A1 `367147.34 to `348622.36 over cost C3. On the basis of net returns over cost C3 for 100 trees, Bhalwal block leads with a value of 363080.85 followed by Ranjan (352951.73). The overall benefit-cost ratio over Cost C3 worked out to be as 5.25:1 under the present value summation method. Among the production constraints, lack of financial resources ranked number 1